â€œThe Mediating Role of Marketing Strategy in the Effect of Antecedents on Export Performance : in the case of of Oil Seeds, Pulses and Coffee Exporting Companies in Ethiopia.â€ - Imiru, Dr. Getie Andualem (Journal of Business Management and Economics, 2018)
This study examined the impact of specific firm, product, industry, and export market characteristics, as well as export marketing strategy (product adaptation, price competitiveness, promotion adaptation and support to foreign distributor) on the export performance On Export Performance of Selected Export Companies in Ethiopia. Data were gathered from 100 marketing strategists via a structured surveyfrom firms engaged in exporting four product categories (coffee, livestock products (leather, live animals and meat), oil seeds and pulses) which has been operating since 1986. The results indicatedthat the four explanatoryvariables have a direct positive and significant effect on overall export performance. Export strategy (product adaptation, price competitiveness and promotion adaptation) also played a significant mediating role on export performance. However, support for distributers strategy has played a positiveand an insignificant role in explaining the export performance. Overall the study finding implied that marketing-mix strategyhas a mediating effect on the relationship. The findings can be generalized only for those sectors studied and provide export managers withuseful insights.